A MOF-derived double-curvature hollow carbon-based wave-absorbing material and a preparation method thereof

CN122940148APending Publication Date: 2026-10-20BEIJING JIAOTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611111720.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-24
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

在单一材料框架内集成双曲率纳米结构(正曲率凸起与负曲率凹陷),为调控电磁能量耗散提供了新思路,但目前在原子尺度上,对纳米材料曲率的选择性调控合成尚未得到探索

Benefits of technology

本发明提供一种MOF衍生双曲率空心碳基吸波材料及其制备方法,该双曲率空心碳材料展现出优秀的电磁波吸收性能(极化位点密度大幅提升),具体优点如下:凹陷的封闭环境限制了离子扩散,延长了电荷滞留时间(弛豫时间增大),导致弛豫过程数量增加(Cole-Cole半圆增加);尖端高曲率加速电荷迁移,但Fe-N4的强配键减缓电荷移动,整体弛豫时间显著增加。尖端与凹陷的微环境差异形成了“尖端-主体-凹陷”多级界面,界面处电荷极化效应叠加。多级碳网络实现了跨曲率界面的电子跃迁,在极低的填充量(14 wt%)下即可实现卓越的电磁波吸收能力,最低反射损耗达到-57 dB。优化后的材料展现出6.95GHz(9.7-16.65 GHz)的超宽有效吸收带宽,覆盖了50%的X波段及全部Ku波段,契合了“薄、轻、宽、强”的吸波材料设计理念。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention provides a MOF-derived hyperbolic hollow carbon-based microwave absorbing material and its preparation method. The method includes: S1, preparing a triazole-based MOF precursor; S2, mixing the triazole-based MOF precursor with dopamine hydrochloride, causing dopamine to polymerize on the surface of the triazole-based MOF precursor to form a polydopamine coating layer; subsequently, carbonizing the resulting product at high temperature in an inert atmosphere to obtain the MOF-derived hyperbolic hollow carbon-based microwave absorbing material. This hyperbolic hollow carbon material exhibits excellent electromagnetic wave absorption performance with a significantly increased polarization site density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electromagnetic wave absorbing materials technology, specifically to a MOF-derived hyperbolic hollow carbon-based absorbing material and its preparation method. Background Technology

[0002] With the increasing severity of electromagnetic radiation pollution, the development of high-performance electromagnetic wave absorbing materials (MAMs) that meet the requirements of being "thin, light, wide, and strong" has become a research hotspot. Metal-organic frameworks (MOFs), due to their tunable porosity and structure, are widely used as precursors for preparing porous carbon-based microwave absorbing materials. Currently, MOF-derived carbon materials typically exhibit regular polyhedral morphologies. To further improve impedance matching and electromagnetic loss capabilities, researchers have attempted to introduce hollow structures or heterogeneous interfaces. However, existing fabrication methods struggle to precisely control the local curvature of the carbon framework at the microscopic level, particularly the inability to simultaneously construct high-curvature tips (positive curvature) and concave structures (negative curvature) on the same monomer.

[0003] Numerous studies have shown that high curvature structures enhance electromagnetic wave dissipation. Integrating bicurvature nanostructures (positive curvature protrusions and negative curvature depressions) within a single material framework offers a novel approach to controlling electromagnetic energy dissipation. However, selective control of nanomaterial curvature at the atomic scale has not yet been explored. The challenge of existing techniques lies in the fact that single curvature surfaces can typically only be achieved by controlling the radius of spherical materials, while integrating multiple (positive and negative) curvature surfaces within the same nanostructure is difficult to accomplish. Summary of the Invention

[0004] To address the aforementioned technical problems, this invention provides a MOF-derived hyperbolic hollow carbon-based microwave absorbing material and its preparation method.

[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows: This invention provides a method for preparing a MOF-derived hyperbolic hollow carbon-based microwave absorbing material. The method includes: S1, preparing a triazole-based MOF precursor; S2, mixing the triazole-based MOF precursor with dopamine hydrochloride, causing dopamine to polymerize on the surface of the triazole-based MOF precursor to form a polydopamine coating layer; and then carbonizing the resulting product at high temperature in an inert atmosphere to obtain the MOF-derived hyperbolic hollow carbon-based microwave absorbing material.

[0006] Further, S2 specifically includes: dispersing a triazole MOF precursor in a water / ethanol mixed solution, adding a tris(hydroxymethyl)aminomethane solution and dopamine hydrochloride for polymerization, so that dopamine polymerizes on the surface of the precursor to form a PDA coating layer, thereby obtaining a PDA-coated precursor; subsequently, the PDA-coated precursor is carbonized at high temperature in an inert atmosphere to obtain a MOF-derived hyperbolic hollow carbon-based microwave absorbing material.

[0007] Furthermore, S2 is carried out according to the following dosage ratios and operating parameters: 100-500 mg of triazolyl MOF precursor; 20-60 mL of water; 50-120 mL of ethanol; 50-150 mM concentration of tris(hydroxymethyl)aminomethane solution; 20-60 mL volume of tris(hydroxymethyl)aminomethane solution; 10%-50% of the mass of triazolyl MOF precursor; polymerization time 0.5-4 h; high-temperature carbonization includes: inert atmosphere of nitrogen or argon; heating rate 1-10 °C / min; carbonization temperature 700-900 °C; holding time 1-4 h.

[0008] Preferably, 200 mg of MET or TM@MET-6, 30 mL of water, and 80 mL of ethanol are stirred for 30 min; 40 mL of 100 mM tris(hydroxymethyl)aminomethane solution is added; then 30 mL of aqueous solution containing 60 mg of dopamine hydrochloride is added, and the mixture is stirred for 60 min; after centrifugation and washing, the product is dried overnight at 60 °C.

[0009] More preferably, for the PDA-coated precursor, the precursor is placed in a tube furnace and heated to 800 °C at 5 °C / min under nitrogen or argon protection, held for 2 h, and then naturally cooled to obtain MOF-derived hyperbolic hollow carbon-based microwave absorbing material.

[0010] Furthermore, S1 also includes: metal modification of the triazole MOF precursor; the metal modification step of the triazole MOF precursor includes: adding the triazole MOF precursor to a methanol solution containing a transition metal salt, stirring at room temperature to introduce metal ions into the triazole MOF precursor, then filtering and drying to obtain a metal-modified triazole MOF precursor; wherein the transition metal salt includes one or more of cobalt salt, iron salt, nickel salt, manganese salt, and copper salt.

[0011] Furthermore, S1 is carried out according to the following dosage ratios and operating parameters: 1-5 g of triazolyl MOF precursor; 100-300 mL of methanol; 1%-20% of the total mass of transition metal salts of triazolyl MOF precursor; stirring time at room temperature for 2-12 h; drying temperature for 80-120 ℃; and drying time for 6-12 h.

[0012] Preferably, when preparing Co@MET-6, 0.144 g of Co(NO3)2·6H2O is dissolved in 200 mL of methanol, 2.0 g of MET-6 is added, the mixture is stirred at room temperature for 6 h, filtered, and then vacuum dried at 100 °C for 8 h.

[0013] When preparing Fe@MET-6, 0.098 g of FeCl2·4H2O was used to replace Co(NO3)2·6H2O, and the remaining steps were the same.

[0014] When preparing multi-metal modified MET-6, two or more metal salts such as Co, Fe, Ni, Mn, and Cu can be added; cobalt salts and iron salts are preferred.

[0015] Further, S1 specifically includes: mixing ethanol, water, ammonium hydroxide and N,N-dimethylformamide to obtain a mixed solvent; adding ZnCl2 to it, stirring to dissolve, and then adding 1H-1,2,3-triazole dropwise, reacting at room temperature to obtain the triazole MOF precursor.

[0016] Furthermore, S1 was carried out according to the following dosage ratios and operating parameters: 40-60 mL of ethanol, 60-90 mL of water, 15-25 mL of ammonium hydroxide, 40-60 mL of N,N-dimethylformamide, 4-6 g of ZnCl2, 5-8 mL of 1H-1,2,3-triazole, reaction time 12-36 h, and reaction temperature at room temperature.

[0017] Preferably, the mixture consists of 50 mL of ethanol, 75 mL of water, 20 mL of ammonium hydroxide, 50 mL of N,N-dimethylformamide, 5.0 g of ZnCl2, and 6.26 mL of 1H-1,2,3-triazole, stirred at room temperature for 24 h.

[0018] Furthermore, before metal modification of the triazole MOF precursor, the triazole MOF precursor is washed and dried. The washing and drying steps of the triazole MOF precursor include: collecting the triazole MOF precursor by filtration or centrifugation, then washing it with ethanol and / or deionized water, and then drying it. The operating parameters include: centrifugation speed 6000-10000 r / min; washing with deionized water 2-5 times; washing with ethanol 2-5 times; drying temperature 60-90 ℃; drying time 6-24 h.

[0019] Preferably, the white product is collected by filtration, washed with ethanol, and dried at 80 °C for 8 h. Alternatively, the precipitate can be collected by centrifugation at 8000 r / min, washed three times with deionized water, washed three times with anhydrous ethanol, and dried under vacuum at 70 °C for 24 h.

[0020] The present invention also provides MOF-derived hyperbolic hollow carbon-based microwave absorbing material prepared by the above-mentioned method for preparing MOF-derived hyperbolic hollow carbon-based microwave absorbing material.

[0021] This invention also provides the application of the above-mentioned MOF-derived hyperbolic hollow carbon-based absorbing material in radar stealth.

[0022] Compared with the prior art, the technical solution provided by the present invention has at least the following advantages: This invention provides a MOF-derived hyperbolic hollow carbon-based microwave absorbing material and its preparation method. This hyperbolic hollow carbon material exhibits excellent electromagnetic wave absorption performance (significantly increased polarization site density), with the following specific advantages: the concave, enclosed environment restricts ion diffusion, prolongs charge retention time (increased relaxation time), leading to an increase in the number of relaxation processes (increased Cole-Cole semicircles); the high curvature at the tip accelerates charge migration, but the strong Fe-N4 bonding slows down charge movement, resulting in a significant increase in the overall relaxation time. The difference in microenvironment between the tip and the concave forms a multi-level interface of "tip-body-concave," where charge polarization effects are superimposed. The multi-level carbon network enables electronic transitions across the curvature interface, achieving excellent electromagnetic wave absorption capability with an extremely low filling amount (14 wt%), and a minimum reflection loss of -57 dB. The optimized material exhibits an ultra-wide effective absorption bandwidth of 6.95 GHz (9.7-16.65 GHz), covering 50% of the X-band and the entire Ku-band, which aligns with the design concept of "thin, light, wide, and strong" absorbing materials. Attached Figure Description

[0023] One or more embodiments are illustrated by way of example with reference to the accompanying drawings. These illustrations do not constitute a limitation on the embodiments, and unless otherwise stated, the figures in the drawings are not to be limited by scale.

[0024] Figure 1 These are the XRD comparison curves of the four samples provided in the embodiments of the present invention; Figure 2 These are SEM images of the four samples provided in the embodiments of the present invention; Figure 3 These are TEM images (including magnified views and corresponding three-dimensional geometric model illustrations of the microstructures) of four samples provided in the embodiments of the present invention. Figure 4 This is a comparison chart of the permeamagnetic parameters of four samples provided in the embodiments of the present invention; Figure 5 This refers to the microwave absorption performance and impedance matching of the four samples provided in the embodiments of the present invention; Figure 6 This invention relates to the electromagnetic attenuation capability and polarization mechanism of four samples provided in the embodiments of the present invention. Figure 7 This is a radar cross-section diagram of the CFP sample provided in an embodiment of the present invention. Detailed Implementation

[0025] In existing technologies, structural control methods are relatively simple, and the overall curvature can only be controlled by changing the template size (such as the radius of a sphere). It is impossible to integrate different types of curvature structures within the same material framework. At the same time, conventional MOF materials are prone to severe structural collapse when directly pyrolyzed. If no special coating strategy is adopted, the pyrolysis products will eventually form amorphous porous carbon foam, thereby losing the electromagnetic loss gain brought by demorphology.

[0026] To address the aforementioned shortcomings, this invention provides a MOF-derived hyperbolic hollow carbon-based microwave absorbing material and its preparation method. This method utilizes the dynamic thermal shrinkage difference between polydopamine (PDA) and triazole MOF (MET), and combines the different coordination abilities of Fe and Co ions with PDA, to simultaneously construct atomically sharpened tips (positive curvature) and recessed regions (negative curvature) in a carbon matrix, thereby obtaining a hollow carbon material with both hyperbolic characteristics, significantly improving its electromagnetic wave absorption performance.

[0027] The present invention will now be described in detail with reference to specific embodiments.

[0028] This invention provides a method for preparing MOF-derived hyperbolic hollow carbon-based microwave absorbing materials, the method comprising: S1: Preparation of the triazole MOF precursor MET-6 Ethanol, water, ammonium hydroxide, and N,N-dimethylformamide were mixed to obtain a mixed solvent; ZnCl2 was added to the solvent, and after stirring to dissolve, 1H-1,2,3-triazole was added dropwise. The mixture was reacted at room temperature to obtain a white MET-6 precursor.

[0029] Actual dosage: 50 mL ethanol, 75 mL water, 20 mL ammonium hydroxide, 50 mL N,N-dimethylformamide, 5.0 g ZnCl2, 6.26 mL 1H-1,2,3-triazole, stirred at room temperature for 24 h.

[0030] Recommended reaction range: 40-60 mL ethanol, 60-90 mL water, 15-25 mL ammonium hydroxide, 40-60 mL N,N-dimethylformamide, 4-6 g ZnCl2, 5-8 mL 1H-1,2,3-triazole, reaction time 12-36 h, reaction temperature room temperature.

[0031] S2: Washing and drying of MET-6 precursor The white product obtained from the reaction was collected by filtration or centrifugation, then washed with ethanol and / or deionized water, and dried to obtain MET-6 white powder.

[0032] Actual conditions: Collect the white product by filtration, wash with ethanol, and dry at 80 ℃ for 8 h. Alternatively, centrifuge at 8000 r / min to collect the precipitate, wash three times with deionized water, wash three times with anhydrous ethanol, and dry under vacuum at 70 ℃ for 24 h.

[0033] Recommended range: centrifugation speed 6000~10000 r / min; washing with deionized water 2~5 times; washing with ethanol 2~5 times; drying temperature 60~90 ℃; drying time 6~24 h.

[0034] S3: Introduction of transition metal ions to prepare TM@MET-6 MET-6 powder was added to a methanol solution containing a transition metal salt and stirred at room temperature to introduce metal ions into the MET-6 precursor. The mixture was then filtered and dried to obtain a metal-modified MET-6 precursor.

[0035] Actual dosage: When preparing Co@MET-6, 0.144 g of Co(NO3)2·6H2O was dissolved in 200 mL of methanol, 2.0 g of MET-6 was added, stirred at room temperature for 6 h, filtered, and then vacuum dried at 100 ℃ for 8 h.

[0036] When preparing Fe@MET-6, 0.098 g of FeCl2·4H2O was used to replace Co(NO3)2·6H2O, and the remaining steps were the same.

[0037] When preparing multi-metal modified MET-6, two or more metal salts such as Co, Fe, Ni, Mn, and Cu can be added.

[0038] Recommended range: MET-6 dosage 1-5 g; methanol dosage 100-300 mL; total transition metal salt dosage 1%-20% of MET-6 mass; stirring time at room temperature 2-12 h; drying temperature 80-120 ℃; drying time 6-12 h.

[0039] The optional metal salts include one or more of cobalt salts, iron salts, nickel salts, manganese salts, and copper salts; cobalt salts and iron salts are preferred.

[0040] S4: PDA coating and high-temperature carbonization to prepare MOF-derived double-curvature hollow carbon-based microwave absorbing materials. First, MET-6 or metal-modified MET-6 is dispersed in a water / ethanol mixture. Then, tris(hydroxymethyl)aminomethane solution and dopamine hydrochloride are added, allowing dopamine to polymerize on the precursor surface to form a PDA coating layer. Subsequently, the resulting product is carbonized at high temperature in an inert atmosphere to obtain MOF-derived hyperbolic hollow carbon-based microwave absorbing material.

[0041] PDA coating dosage: 200 mg MET or TM@MET-6, 30 mL water, 80 mL ethanol, stir for 30 min; add 40 mL of 100 mM tris(hydroxymethyl)aminomethane solution; then add 30 mL of aqueous solution containing 60 mg dopamine hydrochloride, stir for 60 min; after centrifugation and washing, the product is dried overnight at 60 °C.

[0042] Recommended range for PDA coating: MET or TM@MET-6 dosage 100–500 mg; water 20–60 mL; ethanol 50–120 mL; tris(hydroxymethyl)aminomethane solution concentration 50–150 mM; tris(hydroxymethyl)aminomethane solution volume 20–60 mL; dopamine hydrochloride dosage 10%–50% of the mass of MET or TM@MET-6; polymerization time 0.5–4 h; drying temperature 50–80 ℃; drying time 8–24 h.

[0043] Actual conditions for high-temperature carbonization: For PDA-coated precursors, the precursors are placed in a tube furnace and heated to 800 ℃ at a rate of 5 ℃ / min under nitrogen or argon protection, held for 2 h, and then naturally cooled to obtain MOF-derived hyperbolic hollow carbon-based microwave absorbing materials.

[0044] Recommended range for high-temperature carbonization: inert atmosphere is nitrogen or argon; heating rate is 1-10 ℃ / min; carbonization temperature is 700-900 ℃; holding time is 1-4 h.

[0045] Figure 1 The XRD diffraction intensity comparison curves for the four samples are shown. All samples exhibit a broad diffraction pattern within the 2θ range of 20°–30°, typical of amorphous carbon or partially graphitized porous carbon (002) crystal planes. No sharp metallic crystallization peaks for Fe or Co were observed throughout the spectra, indirectly confirming the conclusion that metallic elements exist in the carbon matrix as atomically dispersed sites or extremely small clusters.

[0046] Figure 2 The microscopic particle morphology of the prepared carbon-based materials is visually demonstrated. All samples exhibit micron-sized polyhedral or star-shaped particles. Among them, the CFP sample ( Figure 2 d) It exhibits the most obvious and regular hyperbolic characteristics: the particles not only have sharp outward protrusions (positive curvature), but also obvious inward depressions (negative curvature) on their surface, and the surface has a certain roughness, which provides abundant sites for electromagnetic wave scattering and interface polarization.

[0047] Figure 3 TEM images further confirmed the hollow internal structure of the material. The internal cavities are clearly visible through the thin carbon skeleton. Magnified images and geometric model illustrations visually depict this complex configuration formed by differences in thermal contraction kinetics—atomic-level sharpened tips and collapsed concave surfaces are effectively integrated within the same microscopic framework.

[0048] Figure 4 The complex permittivity and complex permeability of the material were described. Figure 4 (a) and 4(b) show the real (ε') and imaginary (ε'') parts of the complex permittivity. ε' of all samples exhibits typical dispersion behavior, decreasing with increasing frequency. The CP sample has the highest overall values ​​of ε' and ε'', indicating that it has the strongest potential for dielectric polarization and dielectric loss. Figure 4 (c) The dielectric loss tangent (tanδε) further shows that the FP sample exhibits an extremely sharp dielectric loss peak near 11 GHz. Figures 4(d) and 4(e) show the real (μ') and imaginary (μ'') parts of the complex permeability, respectively, and the fluctuations of μ'' directly reflect the magnetic resonance within the material. It can be observed that significant magnetic resonance absorption peaks appear near 8 GHz for CP and near 11 GHz for FP. Figure 4 (f) The magnetic loss tangent (tanδμ) is in high agreement with the μ'' trend, proving that these composite materials (especially FP and CFP) have strong magnetic losses in specific frequency bands.

[0049] Figure 5 The actual absorption performance of the sample was visually evaluated using three-dimensional reflection loss plots (a1-a4), two-dimensional reflection loss contour plots (b1-b4), and characteristic impedance matching plots (c1-c4). The peak values ​​in the three-dimensional plots represent the maximum absorption intensity (RL). min Among them, the FP sample had the strongest absorption extreme value, reaching -52.2 dB (matched thickness 3.5 mm); the CFP sample had the highest absorption RL. min The effective absorption bandwidth (EAB) is -45.4 dB (matched thickness 2.5 mm). The two-dimensional contour plot highlights the effective absorption bandwidth (EAB, i.e., the bandwidth where reflection loss is less than -10 dB). The CFP sample exhibits the best broadband absorption characteristics, with its maximum effective absorption bandwidth (EAB) reaching -45.4 dB. max Up to 6.95 GHz (covering the 9.7-16.65 GHz band). Figure 5(c1-c4) explains the source of this excellent performance: the characteristic impedance matching coefficient (Ms) of CFP and FP can fall well within the ideal range of 0.8-1.2 over a very wide range of frequencies and thicknesses, which means that electromagnetic waves can enter the interior of the material more smoothly rather than being reflected at the surface.

[0050] Figure 6 The internal attenuation mechanism of the materials for electromagnetic waves was analyzed in depth. In Figure 6(d), the attenuation constant (α) generally increases with increasing frequency. CP and CFP maintain high overall attenuation capability throughout the test frequency band, while FP again exhibits a sharp attenuation peak near 11 GHz corresponding to magnetic resonance. The C0 curve in Figure 6(a) is used to identify the source of magnetic loss; its dramatic fluctuations over a wide frequency range indicate that the magnetic loss of these materials is the result of multiple mechanisms, including natural resonance and eddy current loss. Figure 6 (b), (c), (e), and (f) are the Cole-Cole curves for the complex permittivity. Compared to ZP (Figure 6b), which mainly exhibits a linear trend representing conductivity loss, FP, CP, and CFP (especially...) show different trends. Figure 6 The CFP curve in f is composed of multiple distinct overlapping semicircles (as shown by the dashed circle). Each semicircle represents a Debye polarization relaxation process, which strongly demonstrates the existence of extremely rich multiple polarization mechanisms (such as defect polarization or heterogeneous interface polarization) within these composite materials. These polarization relaxation processes greatly enhance the dielectric loss capability of the material. CFP exhibits multiple well-defined continuous semicircles. This indicates the presence of rich heterogeneous interfaces (such as different phase boundaries, defects, functional groups, etc.) within CFP. Different microscopic polarization mechanisms have different response frequencies. When the frequency changes, one polarization mechanism weakens, and another polarization mechanism immediately generates resonant dissipation. The superposition effect of multiple polarization relaxations, combined with its relatively broad magnetic resonance peak ( Figure 4 e), together maintaining the high electromagnetic attenuation constant of CFP over a wider frequency range ( Figure 4 (d's light gray curve), ultimately broadening the absorption bandwidth.

[0051] Analysis of absorption mechanism: Overall, these four samples represent the absorption behavior under different electromagnetic parameter matching states: ZP has a high tendency for conductivity loss ( Figure 6(b) lacks a distinct Cole-Cole semicircle, appearing nearly straight, but lacks sufficient magnetic loss coordination, resulting in mediocre overall absorption intensity (-27.5 dB) and bandwidth. CP has high complex permittivity (ε' and ε''), indicating strong energy storage and dielectric polarization capabilities. However, the high permittivity disrupts the balance between dielectric and permeability, leading to impedance mismatch (electromagnetic waves are more likely to be reflected at the material surface and cannot penetrate the material interior). Therefore, even with a high internal attenuation constant α ( Figure 6 d) Its actual absorption performance is not outstanding. FP exhibits typical "resonance" absorption characteristics. At a specific frequency, dielectric loss and magnetic loss resonate at the same frequency, forming a prominent single-point absorption depth. CFP exhibits "synergistic broadband" absorption characteristics. The dielectric and magnetic parameters are tuned to a suitable ratio, achieving good broadband impedance matching and the superposition of multiple loss mechanisms.

[0052] The CFP sample achieved an effective absorption bandwidth (EAB) of 6.95 GHz (9.7 GHz - 16.65 GHz). Achieving broadband absorption typically requires meeting two key prerequisites: impedance matching across a wide frequency band and multiple attenuation mechanisms covering a broad frequency range. For electromagnetic waves to be absorbed by a material, the first step is to penetrate the material surface and enter the interior with as little reflection as possible. The ε' and ε'' values ​​of the CFP sample were tuned to a moderate level (lower than CP, higher than FP). This "dielectric reduction" treatment effectively reduced surface reflection caused by the skin effect. Observation Figure 5 (c4) The CFP sample has the largest and flattest area of ​​ideal impedance matching contour lines (circled by the white solid circle) in the range of 0.8 to 1.2. This means that with a thickness of about 2.5 mm, electromagnetic waves can penetrate the material relatively smoothly in the frequency band from 9.7 GHz to 16.65 GHz.

[0053] Electromagnetic waves entering the interior of a material need to be converted and dissipated. The reason CFPs can achieve wideband attenuation lies in the heterogeneity of their microscopic interfaces. (Observation) Figure 6 (f) Cole-Cole semicircle plot of CFP. Relay of broadband dissipation: Different microscopic polarization mechanisms have different response frequencies. When the frequency changes, one polarization mechanism weakens, and another immediately produces resonant dissipation. The superposition effect of multiple polarization relaxations, combined with its relatively broad magnetic resonance peak ( Figure 4 e), together maintaining the high electromagnetic attenuation constant of CFP over a wider frequency range ( Figure 6 d), which ultimately broadened the absorption bandwidth.

[0054] The FP sample exhibited a reflection loss of -52.2 dB (absorbing over 99.999% of the electromagnetic wave energy). This absorption depth is typically the result of the combined effects of resonant superposition and phase interference at a specific frequency. Observation Figure 4 In (e) and (f), the imaginary permeability μ'' and magnetic loss tangent tanδμ of the FP sample exhibit a distinct resonance peak near 11 GHz. This indicates that at this frequency, the magnetic domains or magnetic moments within the material undergo natural or exchange resonance, converting magnetic field energy into thermal energy. Simultaneously, observations... Figure 4 (c) The dielectric loss tangent tanδε of the FP sample also shows a significant steep peak around 11 GHz. At this frequency of 11 GHz, dielectric relaxation resonance and magnetic resonance occur simultaneously, resulting in a significant peak in the overall attenuation constant α of the FP sample at this frequency (the bulge of the dark gray curve in Figure 4d). The material thus effectively absorbs electromagnetic wave energy at this frequency.

[0055] The low RL value depends not only on the material's own attenuation but also on macroscopic interference effects. When electromagnetic waves are incident on the absorber surface, part is reflected directly at the air-material interface, while the other part enters the material and is reflected back at the metal plate on the back. The extreme value of the FP sample appears at a specific matching thickness (d = 3.5 mm). At this thickness and a frequency of 11.4 GHz, the phase difference between the electromagnetic wave traveling back and forth inside the material and the electromagnetic wave reflected directly at the surface satisfies the 1 / 4 wavelength destructive interference model condition. This macroscopic phase destructive interference, combined with the microscopic "double resonance" loss of the material at this frequency, causes most of the reflected wave energy to be canceled and dissipated, resulting in an absorption peak of -52.2 dB in the spectrum. This is why such deep absorption is often accompanied by a narrow bandwidth (because the interference and resonance conditions are disrupted if the frequency and thickness deviate from this point).

[0056] Figure 7 This figure shows the three-dimensional directional distribution of the radar cross section (RCS) of a CFP sample as a stealth coating at 13.4 GHz. The scattering intensity is displayed in spherical coordinates as a function of azimuth angle φ and elevation angle θ. The color scale corresponds to the RCS amplitude, with a range of approximately [missing information]. The scattering energy ranges from 25.7 to 14.3 dB·m². Simulation results show that the scattered energy is mainly concentrated in a specific angular direction and exhibits significant attenuation in other directions, indicating that using the CFP sample as a stealth coating can control the scattering path and spatial distribution of incident electromagnetic waves. At 13.4 GHz, the total absorption cross section (ACS) is approximately... 15.06 dB·m², the total radar cross section is approximately The maximum directional RCS is 14.60 dB·m², and the maximum directional RCS is approximately 14.35 dB·m². These results indicate that the CFP coating exhibits a low overall electromagnetic scattering response within the target frequency band, which can be used to reduce the radar detectability of the target.

[0057] Those skilled in the art will understand that the above embodiments are specific examples of implementing the present invention, and in practical applications, various changes in form and detail can be made without departing from the spirit and scope of the present invention. Any person skilled in the art can make their own modifications and alterations without departing from the spirit and scope of the present invention; therefore, the scope of protection of the present invention should be determined by the scope defined in the claims.

Claims

1. A method for preparing a MOF-derived hypercurvature hollow carbon-based microwave absorbing material, characterized in that, The method includes: S1, Preparing triazole MOF precursors; S2. The triazole MOF precursor is mixed with dopamine hydrochloride, and the dopamine is polymerized on the surface of the triazole MOF precursor to form a polydopamine coating layer; then the resulting product is carbonized at high temperature in an inert atmosphere to obtain the MOF-derived hyperbolic hollow carbon-based microwave absorbing material.

2. The method for preparing MOF-derived hypercurvature hollow carbon-based microwave absorbing material according to claim 1, characterized in that, S2 specifically includes: A triazole MOF precursor was dispersed in a water / ethanol mixed solution, and then a tris(hydroxymethyl)aminomethane solution and dopamine hydrochloride were added for polymerization. Dopamine was polymerized on the surface of the precursor to form a PDA coating layer, thus obtaining a PDA-coated precursor. Subsequently, the PDA-coated precursor was carbonized at high temperature in an inert atmosphere to obtain a MOF-derived hyperbolic hollow carbon-based microwave absorbing material.

3. The method for preparing MOF-derived hypercurvature hollow carbon-based microwave absorbing material according to claim 2, characterized in that, S2 should be used according to the following dosage ratios and operating parameters: The dosage of triazolyl MOF precursor is 100–500 mg; water is 20–60 mL; ethanol is 50–120 mL; tris(hydroxymethyl)aminomethane solution concentration is 50–150 mM; tris(hydroxymethyl)aminomethane solution volume is 20–60 mL; and dopamine hydrochloride dosage is 10%–50% of the mass of the triazolyl MOF precursor. Polymerization time: 0.5–4 h; High-temperature carbonization includes: an inert atmosphere of nitrogen or argon; a heating rate of 1–10 °C / min; a carbonization temperature of 700–900 °C; and a holding time of 1–4 h.

4. The method for preparing MOF-derived hypercurvature hollow carbon-based microwave absorbing material according to claim 1, characterized in that, S1 further includes: metal modification of the triazole MOF precursor; The step of metal modification of the triazole MOF precursor includes: adding the triazole MOF precursor to a methanol solution containing a transition metal salt, stirring at room temperature to introduce metal ions into the triazole MOF precursor, and then filtering and drying to obtain the metal-modified triazole MOF precursor; wherein the transition metal salt includes one or more of cobalt salt, iron salt, nickel salt, manganese salt, and copper salt.

5. The method for preparing MOF-derived hypercurvature hollow carbon-based microwave absorbing material according to claim 4, characterized in that, S1 should be used according to the following dosage ratios and operating parameters: The amount of triazole MOF precursor used is 1-5 g; the amount of methanol used is 100-300 mL; the total amount of transition metal salt used is 1%-20% of the mass of triazole MOF precursor; the stirring time is 2-12 h at room temperature; the drying temperature is 80-120 ℃; and the drying time is 6-12 h.

6. The method for preparing MOF-derived hypercurvature hollow carbon-based microwave absorbing material according to claim 1, characterized in that, S1 specifically includes: Ethanol, water, ammonium hydroxide, and N,N-dimethylformamide were mixed to obtain a mixed solvent; ZnCl2 was added to the solvent, and after stirring to dissolve, 1H-1,2,3-triazole was added dropwise. The mixture was reacted at room temperature to obtain the triazole MOF precursor.

7. The method for preparing MOF-derived hypercurvature hollow carbon-based microwave absorbing material according to claim 6, characterized in that, S1 should be used according to the following dosage ratios and operating parameters: 40–60 mL of ethanol, 60–90 mL of water, 15–25 mL of ammonium hydroxide, 40–60 mL of N,N-dimethylformamide, 4–6 g of ZnCl2, 5–8 mL of 1H-1,2,3-triazole, reaction time 12–36 h, reaction temperature room temperature.

8. The method for preparing MOF-derived hypercurvature hollow carbon-based microwave absorbing material according to claim 4, characterized in that, Before metal modification of the triazole MOF precursor, the triazole MOF precursor is washed and dried. The steps of washing and drying the triazole MOF precursor include: collecting the triazole MOF precursor by filtration or centrifugation, then washing it with ethanol and / or deionized water, and then drying it. Operating parameters include: centrifugation speed 6000~10000 r / min; washing with deionized water 2~5 times; washing with ethanol 2~5 times; drying temperature 60~90 ℃; drying time 6~24 h.

9. A MOF-derived hyperbolic hollow carbon-based microwave absorbing material prepared by a method according to any one of claims 1 to 8.

10. An application of the MOF-derived hyperbolic hollow carbon-based absorbing material according to claim 9 in radar stealth.